2003
DOI: 10.1046/j.1460-9568.2003.02500.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of HSV‐mediated gene transfer of nerve growth factor in pyridoxine neuropathy demonstrates functional activity of trkA receptors in large sensory neurons of adult animals

Abstract: The distinct distribution of trkA receptors on small neurons and trkC receptors on large neurons in the dorsal root ganglion correlates with the dependence of these two classes of neurons on nerve growth factor and neurotrophin-3, respectively, for survival during development. In adult animals, the distribution of high affinity neurotrophin (trk) is complex and overlapping; neurotrophins are not required for cell survival, but may influence cell phenotype and the response to injury. In order to test the functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
12
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…Similar results have been reported using an HSV vector engineered to express nerve growth factor in the same model of neuropathy [11]. In a rodent model of type 1 diabetic neuropathy caused by the injection of streptozotocin (a pancreatic β cell toxin), subcutaneous inoculation of an HSV vector expressing nerve growth factor after the onset of diabetes prevents the development of neuropathy [12].…”
supporting
confidence: 76%
“…Similar results have been reported using an HSV vector engineered to express nerve growth factor in the same model of neuropathy [11]. In a rodent model of type 1 diabetic neuropathy caused by the injection of streptozotocin (a pancreatic β cell toxin), subcutaneous inoculation of an HSV vector expressing nerve growth factor after the onset of diabetes prevents the development of neuropathy [12].…”
supporting
confidence: 76%
“…Previous studies demonstrate the utility of replication-defective HSV vectors in the treatment of numerous neurodegenerative disorders of the PNS through the expression of trophic factors, such as nerve growth factor (NGF), neurotrophin 3 (NT-3) and GDNF, [37][38][39][40][41][42][43][44][45] and support their use as therapeutic agents in treating neurological complications of ED. In addition, we have recently demonstrated that replication-defective HSV vectors expressing NT-3 are effective in improving erectile function in rats with chemically induced diabetes mellitus (DM) when the vectors were injected around the cavernous nerve 4 weeks after the induction of DM, 39 although it is not known whether similar gene transfer techniques would be effective for the treatment of ED induced by nerve injury.…”
Section: Introductionmentioning
confidence: 96%
“…5 Expression of neurotrophic factors achieved by HSV-mediated gene transfer is also effective in preventing neuropathy in the pyridoxine and cisplatin models of polyneuropathy in rodents. [6][7][8] Other peptides not conventionally considered to be neurotrophic have been shown to have substantial neuroprotective effects in a variety of models. Vascular endothelial growth factor (VEGF), originally identified by its ability to induce the growth of new blood vessels, 9 can protect neurons from damage induced by ischemia 10,11 and trauma.…”
Section: Introductionmentioning
confidence: 99%